A low water activity solid pre-mix containing hirudin and a method for its preparation

CN122911904APending Publication Date: 2026-10-16BAICENT (HAINAN) TECHNOLOGY CONSULTING CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611282399.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-24
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0003]然而,现有含水蛭素的口服固体制剂开发中,多数方案围绕剂型的释放特性进行设计,常采用湿法制粒、包衣、冷冻干燥等工艺手段实现制剂成型或活性保护,在实际生产与应用中存在多方面局限,湿法制粒与后续高温干燥过程的湿热作用易造成多肽空间结构破坏,导致水蛭素活性出现不可逆的损失;冷冻干燥工艺生产成本高、生产周期长,设备投入大,难以适配大规模的工业化生产需求,对于可直接填充硬胶囊的粉末制剂方案而言,水蛭素活性物在处方整体中占比极低,常规一次性直接混合的方式易出现活性物局部团聚与分布不均,导致单位剂量的活性差异较大;常规辅料组合形成的粉体体系水活度偏高,储存过程中自由水易介导多肽降解反应,造成活性快速衰减;同时多数方案缺乏针对性的酸碱缓冲设计,粉体局部的pH波动会进一步加剧水蛭素的活性降解

Benefits of technology

一、本发明通过海藻糖、甘露醇与胶态二氧化硅形成预吸附分散体系,与水蛭素活性物预先结合,在活性物质表面形成保护性分散层,实现微量活性物质在辅料体系中的初步均匀分散;通过枸橼酸与枸橼酸钠组成的缓冲体系均匀分布于粉体整体中,稳定粉体局部酸碱环境,减少pH波动对多肽空间结构的影响;通过低吸湿性的填充辅料组合构建整体低水活度的粉体体系,控制体系中自由水的占比处于较低水平,减弱水分子介导的多肽降解反应,同时优化粉体的整体物理性能,使预混物具备适配硬胶囊直接填充的流动特性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122911904A_ABST
    Figure CN122911904A_ABST
Patent Text Reader

Abstract

The application discloses a low-water-activity solid premix containing hirudin and a preparation method thereof, relates to the technical field of solid compositions, and comprises the following components: hirudin active substance, trehalose, mannitol, pregelatinized starch, colloidal silicon dioxide, citric acid, sodium citrate, magnesium stearate and microcrystalline cellulose; the application forms a pre-adsorption dispersion system by means of trehalose, mannitol and colloidal silicon dioxide, and the system is combined with the hirudin active substance in advance, so that a protective dispersion layer is formed on the surface of the active substance, and the initial uniform dispersion of trace active substance in the auxiliary material system is realized; the buffer system composed of citric acid and sodium citrate is uniformly distributed in the whole powder, the local acid-base environment of the powder is stabilized, and the influence of pH fluctuation on the spatial structure of polypeptides is reduced; the low-hygroscopicity filling auxiliary material combination is used to construct the whole low-water-activity powder system, the proportion of free water in the system is controlled to be at a low level, and the polypeptide degradation reaction mediated by water molecules is weakened.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of solid composition technology, specifically to a low water activity solid premix containing hirudin and its preparation method. Background Technology

[0002] Hirudin is a class of polypeptide-based natural active substances that can specifically bind to thrombin. Compared with traditional anticoagulants, it has a more precise target and a more direct anticoagulant effect, giving it significant natural advantages in the intervention of thrombosis-related diseases. With the development of polypeptide bioactive substance formulation technology, oral solid dosage forms have become an important dosage form direction for the clinical translation and daily application of hirudin due to their convenient administration and high patient compliance. The industry's development of oral solid dosage forms containing hirudin not only focuses on the effects of the active ingredient, but also places higher demands on the long-term storage stability, production and processing suitability, and quality uniformity of the formulation, driving the continuous optimization and upgrading of related formulation technologies.

[0003] However, in the development of existing oral solid dosage forms containing hirudin, most schemes are designed around the release characteristics of the dosage form, often using processes such as wet granulation, coating, and freeze-drying to achieve formulation shaping or activity protection. These methods have several limitations in actual production and application. The humid heat of wet granulation and subsequent high-temperature drying processes can easily damage the spatial structure of peptides, leading to irreversible loss of hirudin activity. Freeze-drying processes are costly, have long production cycles, and require significant equipment investment, making them unsuitable for large-scale industrial production. For powder formulations that can be directly filled into hard capsules, the proportion of hirudin active ingredient in the overall formulation is extremely low. Conventional one-time direct mixing methods are prone to localized agglomeration and uneven distribution of active ingredients, resulting in significant differences in activity per unit dose. Powder systems formed by conventional excipient combinations tend to have high water activity, and free water easily mediates peptide degradation reactions during storage, causing rapid activity decay. Furthermore, most schemes lack targeted acid-base buffer designs, and local pH fluctuations in the powder can further exacerbate the degradation of hirudin activity. Summary of the Invention

[0004] The purpose of this invention is to overcome the shortcomings of existing technologies and provide a low water activity solid premix containing hirudin and its preparation method. This invention utilizes a pre-adsorption dispersion system formed by trehalose, mannitol, and colloidal silica, which pre-combines with hirudin active ingredients to form a protective dispersion layer on the surface of the active material, achieving preliminary uniform dispersion of trace active ingredients in the excipient system. A buffer system composed of citric acid and sodium citrate is uniformly distributed throughout the powder, stabilizing the local acid-base environment of the powder and reducing the impact of pH fluctuations on the spatial structure of the peptides. A low water activity powder system is constructed using a combination of low-hygroscopic filling excipients, controlling the proportion of free water in the system to a low level, weakening water-mediated peptide degradation reactions, and optimizing the overall physical properties of the powder, giving the premix flow characteristics suitable for direct filling of hard capsules.

[0005] To solve the above-mentioned technical problems, the present invention provides the following technical solution: In one aspect, a low water activity solid premix containing hirudin, wherein the solid premix is ​​a powdered solid premix that can be directly filled into hard capsules, and comprises the following components based on 100% of the total mass of solids excluding water: Hirudin, the active ingredient, has an antithrombin activity of 300,000–1,200,000 ATU / kg; Trehalose 8.0–13.0%; Mannitol 4.0–8.0%; Pregelatinized starch 12.0–20.0%; Colloidal silica 1.0–2.0%; Citric acid 0.20–0.50%; Sodium citrate 0.40–0.90%; Magnesium stearate 0.30–0.70%; Microcrystalline cellulose is the remainder; The solid premix has a water content of 2.5-4.5% and a water activity (aw) of 0.22-0.36.

[0006] Furthermore, the hirudin active ingredient is one or more of natural hirudin, recombinant hirudin, or dried powder containing hirudin; the labeled antithrombin activity of the hirudin active ingredient is ≥10000 ATU / g, preferably ≥20000 ATU / g; the actual feed weight of the hirudin active ingredient is calculated based on the labeled antithrombin activity, and the amount of microcrystalline cellulose is adjusted accordingly to maintain a constant total solids weight.

[0007] Furthermore, the mass ratio of trehalose to mannitol is 1.3 to 2.5:1; the microcrystalline cellulose accounts for 55.0 to 65.0% of the total mass of solids excluding water; and the total mass of the microcrystalline cellulose and pregelatinized starch accounts for 67.0 to 85.0% of the total mass of solids excluding water.

[0008] Furthermore, the mass ratio of citric acid to sodium citrate is 1:1.2 to 3.0; the total mass of citric acid and sodium citrate accounts for 0.60 to 1.40% of the total mass of solids excluding water.

[0009] Furthermore, the angle of repose of the solid premix is ​​35.0–39.5°; the solid premix is ​​filled into No. 0 or No. 00 hard capsules, and the hirudin active ingredient in each hard capsule is 150–600 ATU based on antithrombin activity; the filling amount of each hard capsule is 300–600 mg.

[0010] On the other hand, a method for preparing a low water activity solid premix containing hirudin, the specific steps of which are as follows: Production environment control: The production environment temperature is controlled at 18-25℃, and the relative humidity is ≤35%; Pre-adsorption mixing: Hirudin active ingredient, trehalose, mannitol and colloidal silica are added to a mixing device and mixed for 8-12 minutes to obtain a pre-adsorption mixture; Gradient dilution mixing: Add 20-35% of the total amount of microcrystalline cellulose to the pre-adsorbed mixture and mix in an equal increment to obtain the first mixture; add pregelatinized starch, citric acid, sodium citrate and the remaining microcrystalline cellulose to the first mixture and mix to obtain the second mixture; Lubricating final mixture discharge: Add magnesium stearate to the second mixture, mix, and obtain a low water activity solid premix containing hirudin.

[0011] Furthermore, in the pre-adsorption mixing process, hirudin active ingredient and colloidal silica are added to a mixing device, the mixing device speed is controlled at 15-25 rpm, and the mixture is mixed for 3-5 minutes; then trehalose and mannitol are added, the speed is maintained at 15-25 rpm, and the mixture is continued for 5-7 minutes, with a total mixing time of 8-12 minutes, to obtain the pre-adsorption mixture.

[0012] Furthermore, in the gradient dilution mixing, the equal-incremental mixing method involves adding microcrystalline cellulose to the pre-adsorption mixture in 2 to 3 portions, with the ratio of the mass of microcrystalline cellulose added each time to the mass of the material in the current mixing equipment being 0.2 to 0.5:1; controlling the speed of the mixing equipment to be 12 to 20 rpm; mixing for 3 to 5 minutes after each addition; and the total mixing time after all additions are completed is 10 to 15 minutes to obtain the first mixture.

[0013] Furthermore, in the gradient dilution mixing, pregelatinized starch, citric acid, sodium citrate and the remaining microcrystalline cellulose are added sequentially to the first mixture, the mixing equipment speed is controlled at 12-20 rpm, and the mixing is carried out for 15-25 minutes; the material temperature is maintained at 18-28℃ during the mixing process, and the second mixture is obtained after the mixing is completed.

[0014] Furthermore, in the final lubricating mixture, magnesium stearate is sieved and then evenly sprinkled onto the surface of the second mixture, and the mixing equipment speed is controlled at 8-15 rpm for 2-4 minutes.

[0015] Compared with existing technologies, this low water activity solid premix containing hirudin and its preparation method have the following advantages: I. This invention utilizes a pre-adsorption dispersion system formed by trehalose, mannitol, and colloidal silica to pre-bind with hirudin active ingredients, forming a protective dispersion layer on the surface of the active material, thus achieving preliminary uniform dispersion of trace active ingredients in the excipient system. A buffer system composed of citric acid and sodium citrate is uniformly distributed throughout the powder, stabilizing the local acid-base environment and reducing the impact of pH fluctuations on the spatial structure of the peptides. A low-hygroscopic filler combination constructs a powder system with low overall water activity, controlling the proportion of free water in the system to a low level, weakening water-mediated peptide degradation reactions, and simultaneously optimizing the overall physical properties of the powder, enabling the premix to possess flow characteristics suitable for direct filling of hard capsules.

[0016] II. This invention utilizes a segmented mixing process under low humidity conditions to first pre-adsorb and bind the active material and protective excipients. Then, it gradually adds filler excipients in equal increments for gradient dilution, gradually expanding the powder system while maintaining the uniform distribution of the active material. The entire process is dry mixing, avoiding the damp heat effects of wet granulation and high-temperature drying, thus reducing the loss of hirudin activity during preparation. By matching different mixing stages with corresponding mixing operation methods, the invention balances the degree of mixing uniformity and material stability, completing the preparation of solid premixes under mild conditions, making it suitable for industrialized hard capsule filling production processes.

[0017] Other advantages, objectives and features of the invention will be set forth in part in the description which follows, and in part will be apparent to those skilled in the art from the following examination or study, or may be learned from the practice of the invention. Attached Figure Description

[0018] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the accompanying drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are merely some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without any creative effort.

[0019] Figure 1 A flowchart illustrating a method for preparing a low-water-activity solid premix containing hirudin; Figure 2 This is a framework diagram of the pre-adsorption mixing process in a method for preparing a low water activity solid premix containing hirudin; Figure 3 This is a framework diagram of gradient dilution mixing in a method for preparing a low water activity solid premix containing hirudin. Detailed Implementation

[0020] To further illustrate the technical means and effects of the present invention in achieving its intended purpose, the following detailed description of the specific implementation methods, structures, features, and effects of the present invention, in conjunction with the accompanying drawings and preferred embodiments, is provided below.

[0021] The entire process of this embodiment involves no wet granulation, spray drying, freeze drying, coating, or high-temperature drying. It only employs dry, segmented mixing to prepare a powdered solid premix, which can be directly fed into a hard capsule filling machine for dispensing. All excipients are pharmaceutical-grade powder raw materials conforming to pharmacopoeia standards. The active ingredient, hirudin, is recombinant hirudin dried powder. The outer packaging of the raw material indicates an antithrombin activity of 22000 ATU / g, where "indicated antithrombin activity" refers to the nominal activity value indicated in the raw material's factory quality inspection report; "calibrated antithrombin activity" refers to the amount of material added. The actual activity of the raw materials was obtained from previous measurements. In the examples, the mass of hirudin powder was calculated based on the measured and calibrated activity. The total mass of solids was then adjusted by adding or subtracting microcrystalline cellulose to ensure that the total mass of solids, excluding water, remained constant at 1000g in the examples. Trehalose, mannitol, microcrystalline cellulose, pregelatinized starch, colloidal silica, citric acid, sodium citrate, and magnesium stearate are all conventional pharmaceutical powder excipients. Each excipient carries trace amounts of balanced adsorbed water, which is the only source of moisture in the finished product. No additional liquid water was added during the entire preparation process. Moisture content and water activity are inherent physical indicators of the powder system after equilibrium. Water activity (aw) represents the proportion of free water in the powder that can drive peptide degradation, and the angle of repose is used to characterize the flow properties of the powder; both are inherent properties of the finished product. A three-dimensional motion powder mixer is used for mixing, with a speed that can be precisely controlled from 10 to 30 rpm. The capsule filling equipment is a fully automatic No. 0 hard capsule filling machine. Testing equipment includes a Karl Fischer moisture analyzer, a mirror dew point water activity meter, a fixed funnel angle of repose tester, a peptide activity assay microplate reader, and a multi-point powder sampler. The unified testing operation standards are as follows: moisture content is determined by Karl Fischer volumetric method; water activity is measured by spreading the finished product flat in a sample cup, equilibrating at 25℃ for 30 minutes, and then taking the reading; hirudin antithrombin activity is detected by chromogenic substrate method, and the activity retention rate after preparation is calculated based on the theoretical total activity of hirudin before feeding; for mixing uniformity, 10 points in the upper, middle and lower layers of powder are taken to detect the activity, and the relative standard deviation (RSD) of the activity is calculated; the angle of repose is measured by fixed funnel method, after the powder falls naturally and accumulates to form a conical powder pile, the angle of the inclined plane is measured.

[0022] Example 1 In this example, 1000g of solid powder excluding moisture was prepared. The mass ratio of each component was as follows: total activity of hirudin active ingredient 400,000 ATU, which corresponds to 18.2g of recombinant hirudin dry powder; trehalose 100.0g, mannitol 60.0g, with a mass ratio of 1.67:1; pregelatinized starch 180.0g; colloidal silica 15.0g; citric acid 3.0g, sodium citrate 5.0g, with a mass ratio of 1:1.67; magnesium stearate 5.0g; and microcrystalline cellulose was weighed and added to bring the total solid mass to 1000g. The total mass of microcrystalline cellulose was calculated to be 631.5g, accounting for 63.15% of the total solid mass, and the total mass of microcrystalline cellulose and pregelatinized starch was 811.5g, accounting for 81.15% of the total solid mass.

[0023] Preparation method: Production environment control involves pre-activating the constant temperature and humidity units in the workshop to stabilize the overall temperature at 22℃ and maintain a stable relative humidity of 30%. Before feeding materials, all powder raw materials undergo a 30-minute environmental balancing process to eliminate temperature and humidity differences between the raw materials and the workshop environment, preventing instantaneous moisture absorption and desorption by the powder. Figure 1 As shown; For pre-adsorption mixing, all weighed hirudin active ingredient powder and colloidal silica were added to the hopper of a three-dimensional motion powder mixer. The sealing door was closed, and the mixing speed was set to 20 rpm for 4 minutes to complete the initial dispersion of trace active ingredients and high specific surface area colloidal silica. Then, weighed trehalose and mannitol powders were added at once, and the mixing speed was maintained at 20 rpm for 8 minutes. The total mixing time for the two steps was 12 minutes. After mixing, the hopper was opened and a sample was taken to observe the powder state. There were no obvious agglomerated particles, and a uniformly dispersed pre-adsorption mixture was obtained. Figure 2 As shown; A gradient dilution mixing process was employed. First, 30% of the total mass of microcrystalline cellulose, or 189.45g, was extracted and added in two equal increments to the pre-adsorbed mixture in the mixing drum. After each addition of the corresponding mass of microcrystalline cellulose, the mixing speed was set to 15 rpm and mixed continuously for 4 minutes to obtain a first mixture with uniform powder dispersion. Subsequently, the remaining microcrystalline cellulose, pregelatinized starch, citric acid, and sodium citrate were added to the mixing drum all at once, and the mixture was continuously mixed at 15 rpm for 20 minutes. After mixing, a second mixture was obtained. Figure 3 As shown; For lubrication and final mixing, magnesium stearate is passed through an 80-mesh standard pharmaceutical sieve to remove agglomerated coarse particles and evenly spread on the surface of the second mixture powder. The mixer is set to a speed of 10 rpm and mixed continuously for 3 minutes. After mixing, the material is discharged directly to obtain the finished product, namely a powdered low water activity solid premix containing hirudin.

[0024] After the finished product of Example 1 was allowed to stand and equilibrate for 24 hours, it was tested. The total moisture content of the finished product was 3.2%, the water activity (aw) was 0.26, the angle of repose was 36.1°, the activity retention rate was 92.1%, the relative standard deviation (RSD) of the activity was 3.8%, and the activity distribution uniformity was good. The finished product was put into a fully automatic capsule filling machine, using No. 0 hard capsules, with a single capsule filling amount of 500mg and a total activity of hirudin of 200ATU per capsule. After continuously filling 1000 capsules, the relative standard deviation of the filling amount was measured to be 2.9%, and the filling accuracy was stable, which is suitable for industrial continuous filling production.

[0025] Example 2 In Example 2, 1000g of powder containing solids other than water was prepared. The specific mass ratio of each component was as follows: total activity of hirudin 700,000 ATU; trehalose 120.0g, mannitol 70.0g, with a mass ratio of 1.71:1; pregelatinized starch 190.0g; colloidal silica 16.0g; citric acid 3.5g, sodium citrate 6.0g, with a mass ratio of 1:1.71; magnesium stearate 5.5g; and microcrystalline cellulose was weighed and added to bring the total solids to 1000g. The total mass of microcrystalline cellulose was 589.0g, accounting for 58.90% of the total solids, and the total mass of microcrystalline cellulose and pregelatinized starch was 779.0g, accounting for 77.90% of the total solids.

[0026] Production environment control: The constant temperature and humidity unit is set to 20℃ in the workshop and 28% relative humidity in the workshop. All powder raw materials are pre-balanced in the workshop environment for 30 minutes. For pre-adsorption mixing, hirudin active ingredient and colloidal silica are added to the barrel of a three-dimensional motion powder mixer and mixed at 20 rpm for 4 minutes. Then, trehalose and mannitol are added and mixed at the same speed for 6 minutes. After mixing, a uniformly dispersed pre-adsorption mixture is obtained. The mixture was diluted in a gradient manner. 30% of the total mass of microcrystalline cellulose was added to the mixing drum in three equal increments. After each addition, the mixture was stirred at 12 rpm for 5 minutes. The total mixing time for the three additions was 15 minutes to obtain the first mixture. Then, the remaining microcrystalline cellulose, pregelatinized starch, citric acid, and sodium citrate were added and stirred at 12 rpm for 22 minutes to obtain the second mixture. After lubrication and final mixing, magnesium stearate is passed through an 80-mesh sieve and spread evenly on the surface of the powder. It is mixed at 10 rpm for 3 minutes and then discharged to obtain the finished product, namely a powdered low water activity solid premix containing hirudin.

[0027] After the finished product of Example 2 was allowed to stand and equilibrate for 24 hours, it was tested. The total moisture content of the finished product was 3.6%, the water activity (aw) was 0.30, the angle of repose was 37.2°, the activity retention rate was 91.4%, the relative standard deviation (RSD) of the activity was 4.2%, and the activity distribution uniformity was good. The finished product was put into a fully automatic capsule filling machine, using No. 0 hard capsules, with a single capsule filling amount of 500mg and a total activity of hirudin of 350ATU per capsule. After continuously filling 1000 capsules, the relative standard deviation of the filling amount was measured to be 3.1%, and the filling accuracy was stable, which is suitable for industrial continuous filling production.

[0028] Example 3 In Example 3, 1000g of powder containing solids other than water was prepared. The specific mass ratio of each component was as follows: total activity of hirudin active ingredient 1,000,000 ATU; trehalose 90.0g, mannitol 50.0g, with a mass ratio of 1.80:1; pregelatinized starch 185.0g; colloidal silica 13.0g; citric acid 2.5g, sodium citrate 5.0g, with a mass ratio of 1:2.00; magnesium stearate 4.5g; and microcrystalline cellulose was added to make up to 1000g of total solids. The total mass of microcrystalline cellulose was 649.5g, accounting for 64.95% of the total solids, and the total mass of microcrystalline cellulose and pregelatinized starch was 834.5g, accounting for 83.45% of the total solids.

[0029] Production environment control: workshop temperature is constant at 24℃, relative humidity is stable at 33%, and all powder raw materials are placed in the workshop for 30 minutes in advance to achieve equilibrium. Pre-adsorption mixing: Hirudin active ingredient and colloidal silica are added to the barrel of a three-dimensional motion powder mixer and mixed at 20 rpm for 4 min. Then, trehalose and mannitol are added and mixed for another 4 min. The total mixing time is 8 min to obtain the pre-adsorption mixture. The mixture was diluted in a gradient manner. 30% of the total amount of microcrystalline cellulose was added in two equal increments, and the mixture was stirred at 15 rpm for 4 minutes each time to obtain the first mixture. The remaining microcrystalline cellulose, pregelatinized starch, citric acid and sodium citrate were added and stirred at 15 rpm for 18 minutes to obtain the second mixture. After lubrication and final mixing, magnesium stearate is evenly spread on the surface of the powder after passing through an 80-mesh sieve. It is mixed at 8 rpm for 2 minutes, and the finished product, namely a powdered low water activity solid premix containing hirudin, is obtained.

[0030] After the finished product of Example 3 was allowed to stand and equilibrate for 24 hours, it was tested. The total moisture content of the finished product was 4.0%, the water activity aw was 0.34, the angle of repose was 38.4°, the activity retention rate was 90.6%, the relative standard deviation of activity was 4.7%, and the activity distribution uniformity was good. The finished product was put into a fully automatic capsule filling machine, using No. 0 hard capsules, with a single capsule filling amount of 500mg and a single capsule hirudin total activity of 500ATU. After continuously filling 1000 capsules, the relative standard deviation of the filling amount was measured to be 3.4%, and the filling accuracy was stable, which is suitable for industrial continuous filling production.

[0031] Comparative Example 1 The raw material ratio is the same as in Example 1, except that trehalose, mannitol, and colloidal silica are removed, and the missing components are all made up with microcrystalline cellulose. The pre-adsorption mixing and equal incremental gradient dilution steps are eliminated in the preparation process. All powders are put into the mixer at one time for uniform mixing. The remaining environmental parameters, mixing speed, and mixing time are exactly the same as in Example 1, and the final product is obtained.

[0032] After the finished product of Comparative Example 1 was allowed to stand and equilibrate for 24 hours, it was tested using the same methods as in Example 1. The total moisture content of the finished product was 5.1%, the water activity (aw) was 0.43, the angle of repose was 42.8°, the activity retention rate was 76.4%, the relative standard deviation (RSD) of the activity was 8.9%, and the uniformity of the activity distribution was poor. The No. 0 hard capsules were filled under the same conditions as in Example 1, with a single capsule filling amount of 500mg. 1000 capsules were filled continuously, and the relative standard deviation of the filling amount was measured to be 6.8%, indicating large fluctuations in filling accuracy and insufficient stability in continuous production.

[0033] Comparative Example 2 The raw material ratio and segmented mixing process are completely consistent with Example 1, except that the low humidity control in the workshop is cancelled, the relative humidity of the production environment is maintained at 58%, and the other process parameters remain unchanged, and the final product is obtained.

[0034] After the finished product of Comparative Example 2 was allowed to stand and equilibrate for 24 hours, it was tested using the same methods as in Example 1. The total moisture content of the finished product was 5.8%, the water activity (aw) was 0.49, the angle of repose was 44.3°, the activity retention rate was 72.9%, the relative standard deviation (RSD) of the activity was 7.6%, and the uniformity of the activity distribution was poor. The No. 0 hard capsules were filled under the same conditions as in Example 1, with a single capsule filling amount of 500 mg. 1000 capsules were filled continuously, and the relative standard deviation of the filling amount was measured to be 7.2%. The fluidity decreased after moisture absorption, occasional sticking and bubbling occurred during the filling process, and the filling amount accuracy fluctuated significantly.

[0035] Comparative Example 3 The raw material ratio and all preparation processes are completely consistent with those in Example 1, except that citric acid and sodium citrate buffer components are removed, and the missing mass is made up with microcrystalline cellulose. All other operating parameters remain unchanged, and the final product is obtained.

[0036] After the finished product of Comparative Example 3 was allowed to stand and equilibrate for 24 hours, it was tested using the same methods as in Example 1. The total moisture content of the finished product was 3.5%, the water activity (aw) was 0.31, and the angle of repose was 37.6°. The moisture content, water activity, and flowability were close to those of Example 1. The relative standard deviation (RSD) of the activity was 4.5%. The No. 0 hard capsules were filled using the same conditions as in Example 1, with a single capsule filling weight of 500 mg. 1000 capsules were filled continuously, and the relative standard deviation of the filling weight was measured to be 3.6%, which was close to that of Example 1. However, the activity retention rate of Comparative Example 3 after preparation was 80.1%. The local acid-base environment of the finished product lacked buffer control, and the activity loss of hirudin was greater during the preparation process.

[0037] In summary, the moisture content, water activity, and angle of repose of the finished products in the three sets of examples were all at high levels, the relative standard deviation of hirudin activity distribution was low, the activity retention rate during the preparation process was high, and they were suitable for direct filling of hard capsules with stable filling accuracy and balanced overall performance. The finished product of Comparative Example 1, which removed the protective excipient combination and the graded mixing process, showed decreased fluidity, worse activity distribution uniformity, and increased activity loss during the preparation process. The finished product of Comparative Example 2, which did not control the humidity of the production environment, showed a significant increase in water activity after moisture absorption, the most prominent hirudin activity loss, and the largest fluctuation in capsule filling volume. The finished product of Comparative Example 3, which removed the acid-base buffer component, showed deterioration in both activity retention rate and distribution uniformity. The test results clearly demonstrate the influence of various factors on the performance of hirudin-containing solid premixes. The combination of low humidity environment, protective excipients, buffer system, and graded mixing process can effectively improve the overall quality and processing adaptability of the finished product.

[0038] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some modifications or alterations to the above-disclosed technical content to create equivalent embodiments without departing from the scope of the present invention. Any simple modifications, equivalent changes and alterations made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the scope of the present invention.

Claims

1. A low water activity solid premix containing hirudin, characterized in that, The solid premix is ​​a powdered solid premix that can be directly filled into hard capsules, and contains the following components based on 100% of the total solids excluding water: Hirudin, the active ingredient, has an antithrombin activity of 300,000–1,200,000 ATU / kg; Trehalose 8.0–13.0%; Mannitol 4.0–8.0%; Pregelatinized starch 12.0–20.0%; Colloidal silica 1.0–2.0%; Citric acid 0.20–0.50%; Sodium citrate 0.40–0.90%; Magnesium stearate 0.30–0.70%; Microcrystalline cellulose is the remainder; The solid premix has a water content of 2.5-4.5% and a water activity (aw) of 0.22-0.

36.

2. The low water activity solid premix containing hirudin according to claim 1, characterized in that, The hirudin active ingredient is one or more of natural hirudin, recombinant hirudin, or dried powder containing hirudin; the labeled antithrombin activity of the hirudin active ingredient is ≥10000 ATU / g, preferably ≥20000 ATU / g.

3. The low water activity solid premix containing hirudin according to claim 1, characterized in that, The mass ratio of trehalose to mannitol is 1.3 to 2.5:1; the microcrystalline cellulose accounts for 55.0 to 65.0% of the total solids excluding water; and the total mass of the microcrystalline cellulose and pregelatinized starch accounts for 67.0 to 85.0% of the total solids excluding water.

4. The low water activity solid premix containing hirudin according to claim 1, characterized in that, The mass ratio of citric acid to sodium citrate is 1:1.2 to 3.0; the total mass of citric acid and sodium citrate accounts for 0.60 to 1.40% of the total mass of solids excluding water.

5. The low water activity solid premix containing hirudin according to claim 1, characterized in that, The angle of repose of the solid premix is ​​35.0 to 39.5°; the solid premix is ​​filled into No. 0 or No. 00 hard capsules, and the hirudin active ingredient in each hard capsule is 150 to 600 ATU based on antithrombin activity; the filling amount of each hard capsule is 300 to 600 mg.

6. A method for preparing a low water activity solid premix containing hirudin, the method being applicable to the low water activity solid premix containing hirudin as described in any one of claims 1 to 5, characterized in that, The specific steps of this method are as follows: Production environment control: The production environment temperature is controlled at 18-25℃, and the relative humidity is ≤35%; Pre-adsorption mixing: Hirudin active ingredient, trehalose, mannitol and colloidal silica are added to a mixing device and mixed for 8-12 minutes to obtain a pre-adsorption mixture; Gradient dilution mixing: Add 20-35% of the total amount of microcrystalline cellulose to the pre-adsorbed mixture and mix in an equal increment to obtain the first mixture; add pregelatinized starch, citric acid, sodium citrate and the remaining microcrystalline cellulose to the first mixture and mix to obtain the second mixture; Lubricating final mixture discharge: Add magnesium stearate to the second mixture, mix, and obtain a low water activity solid premix containing hirudin.

7. The method for preparing a low water activity solid premix containing hirudin according to claim 6, characterized in that, In the pre-adsorption mixing process, hirudin active ingredient and colloidal silica are added to a mixing device, and the mixing device speed is controlled at 15-25 rpm for 3-5 minutes. Then, trehalose and mannitol are added, and the speed is maintained at 15-25 rpm for 5-7 minutes. The total mixing time is 8-12 minutes to obtain the pre-adsorption mixture.

8. The method for preparing a low water activity solid premix containing hirudin according to claim 6, characterized in that, In the gradient dilution mixing, the equal-increment mixing method involves adding microcrystalline cellulose to the pre-adsorption mixture in 2 to 3 portions, with the ratio of the mass of microcrystalline cellulose added each time to the mass of the material in the mixing equipment being 0.2 to 0.5:1; controlling the speed of the mixing equipment to be 12 to 20 rpm; mixing for 3 to 5 minutes after each addition; and the total mixing time after all additions are completed is 10 to 15 minutes to obtain the first mixture.

9. The method for preparing a low water activity solid premix containing hirudin according to claim 6, characterized in that, In the gradient dilution mixing process, pregelatinized starch, citric acid, sodium citrate and the remaining microcrystalline cellulose are added sequentially to the first mixture. The mixing equipment speed is controlled at 12-20 rpm and the mixture is mixed for 15-25 minutes. During the mixing process, the material temperature is maintained at 18-28℃. After the mixing is completed, the second mixture is obtained.

10. The method for preparing a low water activity solid premix containing hirudin according to claim 6, characterized in that, In the final lubricating mixture discharge, magnesium stearate is sieved and then evenly sprinkled onto the surface of the second mixture. The mixing equipment speed is controlled at 8-15 rpm, and the mixture is mixed for 2-4 minutes.